Bevacizumab in glioblastoma multiforme. Issue 1 (January 2012) - Specenier, Pol
Bevacizumab is a humanized IgG1 monoclonal antibody that selectively binds with high affinity to human VEGF and neutralizes VEGF'' s biologic activity. Malignant gliomas are characterized by extensive microvascular proliferation and produce VEGF. Preclinical data indicate that angiogenesis is essential for the proliferation and survival of malignant glioma cells. Promising response rates, progression-free survival rates at 6 months and median overall survival in patients with recurrent glioblastoma multiforme (GBM) have been reported with bevacizumab, both in retrospective analyses and in prospective Phase II studies. In the pivotal randomized but noncomparative Phase II trial, a non-negligible percentage of patients survived beyond 1 and 2 years after the start of bevacizumab administration. However, randomized Phase III trial data on bevacizumab in recurrent GBM are lacking. Currently, bevacizumab is being studied in combination with temozolomide and radiation in previously untreated GBM patients in two large randomized Phase III trials.